Age-Friendly Health Systems Integration into Rural Primary Care Clinics: A Journey of One Geriatric Workforce Enhancement Program - Leah Tobey-Moore PT, DPT, MBA; Katherine Scalzo; Stacie Massey MA, CHW; Robin McAtee PhD, RN, FACHE (SAGE Publishing, 2024)
This study explores the implementation of the Age-Friendly Health Systems (AFHS) 4Ms Framework into primary care clinics in rural Arkansas, facilitated by the AGEC and funded by The Health Resources and Services Administration's Geriatric Workforce Enhancement Program (GWEP) grant. Implementation success is evaluated by monitoring merit-based incentive payment system (MIPS) measures and other variables, providing insight into the effectiveness of integrating AFHS and enhancing older adult care. AGEC employed implementation strategies (train-the-trainer, audit and feedback, and clinical reminders using Electronic Medical Record (EMR)), the i-PARIHS implementation framework, and the RE-AIM evaluation framework to facilitate integration of the AFHS 4Ms Framework into partnered rural federally qualified healthcare clinics (FQHC). AGEC aimed to equip the healthcare workforce through comprehensive training sessions and resource provision. Additionally, the EMR system modifications guided clinicians in aligning care with the AFHS 4Ms Framework. This multifaceted approach ensured a systematic and tailored implementation, enhancing the capacity of rural FQHCs in Arkansas to deliver Age-Friendly care. Improvements were observed in MIPS outcome measures, including increased completion of fall and depression screens, Annual Wellness Visits (AWV) and Advance Care Plans (ACP). These changes reflect a proactive impact on comprehensive care delivery for older adults. Since adopting the AFHS 4Ms Framework, these rural Arkansas FQHC clinics have significantly enhanced their older adult care, earning recognition as AFHS Clinics by the Institute for Health Improvement (IHI). Primary care practices nationwide can implement similar evidence-based approaches to improve care for the expanding older adult population in the U.S.